The Existence and Uniqueness of Solutions and Lyapunov-Type Inequality for CFR Fractional Differential Equations - Xia Wang; Run Xu (Journal of Function Spaces)
In this paper, we research CFR fractional differential equations with the derivative of order 3<α<4. We prove existence and uniqueness theorems for CFR-type initial value problem. By Green’s function and its corresponding maximum value, we obtain the Lyapunov-type inequality of corresponding equations. As for application, we study the eigenvalue problem in the sense of CFR.